Fiber Post Cementation Strategies: Effect of Mechanical Cycling on Push-out Bond Strength and Cement Polymerization Stress - Bergoli, Cesar Dalmolin [UNESP]; Amaral, Marina [UNESP]; Cidreira Boaro, Leticia Cristina; Braga, Roberto Ruggiero; Valandro, Luiz Felipe (Quintessence Publishing Co Inc, 2012)
Purpose: To evaluate the effect of mechanical cycling and cementation strategies on the push-out bond strength between fiber posts and root dentin and the polymerization stresses produced using three resin cements.Materials and Methods: Eighty bovine mandibular teeth were sectioned to a length of 16 mm, prepared to 12 mm, and embedded in self-curing acrylic resin. The specimens were then distributed into 8 groups (n = 10): Gr1 - Scotchbond Multi Purpose + RelyX ARC; Gr2 - Scotchbond Multi Purpose + RelyX ARC + mechanical cycling; Gr3 - AdheSE + Multilink Automix; Gr4 - AdheSE + Multilink Automix + mechanical cycling; Gr5 - phosphoric acid + RelyX U100 (self-adhesive cement); Gr6 - phosphoric acid+ RelyX U100 + mechanical cycling; Gr7 - RelyX U100; Gr8 - RelyX U100 + mechanical cycling. The values obtained from the push-out bond strength test were submitted to two-way ANOVA and Tukey's test (p = 0.05), while the values obtained from the polymerization stress test were subjected to one-way ANOVA and Tukey's test (alpha = 0.05).Results: Mechanical cycling did not affect the bond strength values (p = 0.236), while cementation strategies affected the push-out bond strength (p < 0.001). Luting with RelyX U100 and Scotch Bond Multi Purpose + RelyX ARC yielded higher push-out bond strength values. The polymerization stress results were affected by the factor "cement" (p = 0.0104): the self-adhesive cement RelyX U100 exhibited the lowest values, RelyX ARC resulted in the highest values, while Multi link Automix presented values statistically similar to the other two cements.Conclusion: The self-adhesive cement appears to be a good alternative for luting fiber posts due to the high push-out bond strengths and lower polymerization stress values.
Keywords: cementation; fiber posts; mechanical cycling